2021
DOI: 10.1093/aob/mcab104
|View full text |Cite
|
Sign up to set email alerts
|

Root hair phenotypes influence nitrogen acquisition in maize

Abstract: Background and Aims The utility of root hairs for nitrogen (N) acquisition is poorly understood. Methods We explored the utility of root hairs for N acquisition in the functional-structural model SimRoot and with maize genotypes with variable root hair length (RHL) in greenhouse and field environments. Key Results Simulation results indicate that long, dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Studies of wild grasses reported shorter root hairs with increased N availability ( Boot and Mensink, 1990 ). Recently a modeling approach indicated that root hairs are important during N deficiency ( Saengwilai et al , 2021 ). We conclude that root hair length is a trait worthy of further investigation for more N-efficient varieties, and that plant development is an important variable for full understanding of the contribution of length.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of wild grasses reported shorter root hairs with increased N availability ( Boot and Mensink, 1990 ). Recently a modeling approach indicated that root hairs are important during N deficiency ( Saengwilai et al , 2021 ). We conclude that root hair length is a trait worthy of further investigation for more N-efficient varieties, and that plant development is an important variable for full understanding of the contribution of length.…”
Section: Discussionmentioning
confidence: 99%
“…An excellent example of a direct effect of root anatomy on soil resource capture is that of root hairs. Variation in root hair length and density is associated with the volume of the diffusion depletion zone surrounding roots, and therefore with the exploitation of rhizosphere resources, including most notably P ( Bates and Lynch, 2000 ), which is highly immobile in the soil, but also including nitrate, a mobile resource ( Saengwilai et al, 2021 ). Anatomical phenes that reduce the metabolic cost of soil exploration often improve soil resource capture ( Lynch, 2015 , 2019 ; Lynch et al, 2021 ).…”
Section: Root Phenotypes As Breeding Targets To Develop Crops That Ar...mentioning
confidence: 99%
“…and nitrogen (Saengwilai et al, 2021), while incurring little metabolic cost (Bates & Lynch, 2000b). Xylem vessels are another anatomical feature that are responsible for the bulk of axial transport of water and nutrients through the root system.…”
Section: Crop Sciencementioning
confidence: 99%
“…Root hairs are subcellular outgrowths of epidermal cells and are another anatomical phene that expand the volume of soil foraged in the rhizosphere. Root hairs have been shown in modeling and empirical studies to benefit the capture of immobile nutrients like phosphorus (Bates & Lynch, 2000a; Gahoonia & Nielsen, 1998; Miguel et al., 2015) as well as mobile resources like water (Carminati et al., 2017), and nitrogen (Saengwilai et al., 2021), while incurring little metabolic cost (Bates & Lynch, 2000b). Xylem vessels are another anatomical feature that are responsible for the bulk of axial transport of water and nutrients through the root system.…”
Section: Introductionmentioning
confidence: 99%